The Role of Membrane Phosphoglycerate Kinase in the Control of Glycolytic Rate by Active Cation Transport in Human Red Blood Cells - Parker, John C. (The Rockefeller University Press, 1967)
When the internal Na of human red cells is raised, both K influx and lactate production increase and become more sensitive to the inhibitory action of ouabain. This occurs with either glucose or purine nucleoside as substrate. Fresh whole hemolysates enriched with Na and Mg will convert intermediates above the triose phosphate dehydrogenase step to lactate at a rate which is slowed by ouabain. Intermediates beyond the phosphoglycerate kinase step (PGK) are metabolized at a very rapid rate which is not affected by ouabain. No metabolic effects of ouabain were found in ghost-free hemolysates. Hemoglobin-free ghosts were shown to have both triose phosphate dehydrogenase and PGK activity. The rate of this two-enzyme sequence was found to be a function of the ADP concentration, being maximal when ADP > 0.35 mM. Initial addition of ATP to the ghost system rendered the forward rate of the sequence sensitive to the inhibitory action of ouabain. When the sequence was run in reverse, no inhibitory effect of ouabain could be demonstrated. It is concluded that membrane PGK is a point at which the Na-K transport system can influence the metabolic rate and that this action is possibly exerted via a compartmentalized form of ADP which is an immediate substrate for the ghost PGK.